Creating identity : the popular romance heroine's journey to selfhood and self-representation - Kamble, Jayashree, 1977- (Indiana University Press, 2023)
"In Creating Identity, Jayashree Kamblé examines the romance genre, with its timely flexibility to keep what audiences find desirable and discard what is not, by asking an important question: "Who is the romance heroine, and what does she want?" To find the answer, Kamblé explores how heroines in ten novels reject societal labels and instead define themselves on their own terms with their own agency. Using a truly intersectional approach, Kamblé combines gender and sexuality, Marxism, critical race theory, and literary criticism to survey various aspects of heroines' identities, such as sexuality, gender, work, citizenship, and race. Ideal for readers interested in gender studies and literary criticism, Creating Identity highlights a genre in which heroines do not accept that independence and strong, loving relationships are mutually exclusive but instead demand both, echoing the call from the very readers who have made this genre so popular"--